Immunogenicity Studies in Carnivores Using a Rabies Virus Construct with a Site-Directed Deletion in the Phosphoprotein. (21st September 2011) - Vos, Ad; Conzelmann, Karl-Klaus; Finke, Stefan; Müller, Thomas; Teifke, Jens; Fooks, Anthony R.; Neubert, Andreas
Abstract : Different approaches have been applied to develop highly attenuated rabies virus vaccines for oral vaccination of mesocarnivores. One prototype vaccine construct is SAD dIND1, which contains a deletion in the P-gene severely limiting the inhibition of type-1 interferon induction. Immunogenicity studies in foxes and skunks were undertaken to investigate whether this highly attenuated vaccine would be more immunogenic than the parental SAD B19 vaccine strain. In foxes, it was demonstrated that SAD dIND1 protected the animals against a rabies infection after a single oral dose, although virus neutralizing antibody titres were lower than in foxes orally vaccinated with the SAD B19 virus as observed in previous experiments. In contrast, skunks receiving 10 7.5 FFU SAD dIND1 did not develop virus neutralizing antibodies and were not protected against a subsequent rabies infection.